Fire Hazard Assessment During Construction of A Mixed-Use Development Project In Kuala Lumpur - Zakaria, Zaamuddin; Ismail, Syuhaida; Nurul Mardiah Wan Mohd. Rani, Wan; Che Amat, Rohayah; Hussaini Wahab, Mohammad (International Journal of Engineering and Technology, 2018)
Construction by nature is inherently dangerous, with a high degree of hazard and risk. Serious fire has occurred in building under construction, which will not delay their completion dates and loss of life, but also result in serious monetary losses. The objectives of this paper are to investigate the causes of fire hazard during the construction phase; assess the risk level arising from the fire hazard during the construction phase; and tpropose safety control measures of fire hazard during the construction phase. Primary data is obtained from the respondents of a mixed use development project in Kuala Lumpur via questionnaire surveys. The data is analysed via Statistical Package for the Social Science (SPSS) and Hazard Identification, Risk Assessment and Risk Control (HIRARC). The findings show that the most important causes of fire hazard of a mixed-use development project are related to workers site activities. Meanwhile, HIRARC identifies that fire hazard from hot works and use electrical tools are the most important risks. Lastly, safety control measures were proposed to control the identified fire hazard by improving the operating procedure of hot works and use of electrical tools as well as implementing good housekeeping practices and inspection at the workplace.